PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN SEKOLAH BERBASIS EXCEL PADA MTS MUHAMMADIYAH SE-KOTA MALANG - Mudrifah, Mudrifah; Ulum, Ihyaul; Dwi Mawardi, Fahmi (COVIT (Community Service of Tambusai), 2023)
Schools under the Muhammadiyah Regional Leadership (PDM) in Malang City still vary in their financial governance implementation and are not in accordance with financial reporting standards according to PSAK 45. This happens because there are no standard standards that have been imposed by PDM or the higher institution is the East Java Muhammadiyah Regional Leadership (PWM). Guidelines for school financial management have not been effectively enforced or required for any Muhammadiyah charity efforts. So that most of the schools under Muhammadiyah’s charitable efforts do not understand financial reporting in accordance with applicable accounting standards and are still manual. The purpose of this community service is for MTs Muhammadiyah schools in Malang City to be able to prepare financial reports according to generally accepted accounting principles and to be able to fulfill financial reporting obligations in accordance with applicable laws and regulations. In addition, partners can create, use and understand excel-based school financial reporting. Keywords: financial management, financial reporting, microsoft excel, MTs muhammadiyah, malang city